Dose–response relationship between body mass index and risks of all-cause mortality and disability among the elderly: A systematic review and meta-analysis. Issue 4 (August 2019) - Jiang, Mingjun; Zou, Yongqiu; Xin, Qinghua; Cai, Yuanfa; Wang, Ying; Qin, Xueying; Ma, Defu
Summary: Background & aims: To establish the relationship between body mass index (BMI) and risks of mortality and disability among the Elderly. Methods: A systematic review and dose–response meta-analysis was performed. PubMed, Embase, Cochrane library, and Google Scholar were searched systematically until December 2017 for relative studies reporting the hazard ratio (HR) and corresponding 95% confidence intervals (CIs) of all-cause mortality or disability across different BMI categories. Results: 44 studies (37 studies on all-cause mortality and 9 studies on disability) were included in the meta-analysis. The restricted cubic spline model presents a U-shape trend, which suggests a relationship between BMI and all-cause mortality. As BMI increased, the all-cause mortality decreased from 1.49 (95% CI: 1.31, 1.71) to 0.96 (95% CI: 0.93, 0.98) in the 14.0–27.9 range and increased from 0.96 (95% CI: 0.94, 0.99) to 1.95 (95% CI: 1.37, 2.77) in the 28.0–47.9 range. In comparison with the reference BMI (23.0–23.9), the 24.0–29.0 BMI presented a significant protective effect, whereas <23.0 BMI and >33.0 BMI presented a significant risk effect on all-cause mortality. For disability, the restricted cubic spline model shows a nonlinear relationship. Individuals with >28.0 BMI and 33.0 BMI were 19% (95% CI: 1.01, 1.40) and 43% (95% CI: 1.13, 1.82) more prone to disability risks compared with those in the reference group, respectively. Conclusions: The lower-end recommended BMI range, underweight, and obesity among the elderly is associated with significantly increased risks of mortality and disability. The 23.0–28.0 BMI range may be the healthy weight range for the elderly group.